The clinical potential of frailty indicators on identifying recurrent fallers in the community – The Mr. Os and Ms. OS cohort study in Hong Kong - Lam, Freddy M. H. (J Am Med Dir Assoc, 2019)
OBJECTIVES: To compare the clinical value of three frailty indicators in a screening pathway for identifying older men and women who are at risk of falls. DESIGN: A prospective cohort study. SETTING AND PARTICIPANTS: Four thousand Chinese adults (2000 men) aged 65 years or above were recruited from the community in Hong Kong. METHODS: The Cardiovascular Health Study Criteria (CHS), the FRAIL scale, and the Study for Osteoporosis and Fracture Criteria (SOF) were included for evaluation. Fall history was used as a comparative predictor. Recurrent falls during the second year after baseline was the primary outcome. The area under the receiver operating characteristic curve (AUC) was used to evaluate the ability of the frailty indicators and fall history to predict recurrent falls. Independent predictors identified in logistic regression were put in the Classification and Regression Tree (CART) analysis to evaluate their performance in screening high-risk fallers. RESULTS: Fall history predicts recurrent falls in both men and women (AUC: men=0.681; women=0.645) better than all frailty indicators (AUC≤0.641). After adjusting for fall history, only FRAIL (AUC=0.676) and SOF (AUC=0.673) remained as significant predictors for women while no frailty indicator remained significant in men. FRAIL could classify older women into two groups with distinct chances of being a recurrent faller in people with no fall history (3.8% vs 7.5%), a single fall history (9.5% vs 37.5%), and history of recurrent falls (16.0% vs 30.8%). SOF has limited ability in identifying recurrent fallers in the group of elderly with a single fall history (no fall history: 3.9% vs 8.6%; single fall history: 10.2% vs 10.9%; history of recurrent falls: 16.5% vs 20.6%). CONCLUSION AND IMPLICATION: SOF and FRAIL could provide some additional prediction value to fall history in older women but not men. FRAIL could be clinically useful in identifying older women at risk of recurrent falls, especially in those with a single fall history.